Corporate Foresight and Dynamic Capabilities: An Exploratory Study - Lisa-Marie Semke; Victor Tiberius (Forecasting, 2020)
Firms engage in forecasting and foresight activities to predict the future or explore possible future states of the business environment in order to pre-empt and shape it (corporate foresight). Similarly, the dynamic capabilities approach addresses relevant firm capabilities to adapt to fast change in an environment that threatens a firm’s competitiveness and survival. However, despite these conceptual similarities, their relationship remains opaque. To close this gap, we conduct qualitative interviews with foresight experts as an exploratory study. Our results show that foresight and dynamic capabilities aim at an organizational renewal to meet future challenges. Foresight can be regarded as a specific activity that corresponds with the sensing process of dynamic capabilities. The experts disagree about the relationship between foresight and sensing and see no direct links with transformation. However, foresight can better inform post-sensing activities and, therefore, indirectly contribute to the adequate reconfiguration of the resource base, an increased innovativeness, and firm performance.